A Reflection on Challenges Faced by Deaf Trainees in Effective Social Interaction in St. Angela Mumias Vocational School, Kakamega, Kenya - Mumbua Nzioka Nzioka, Brenda; Ouko, Ong’ang’a; Backy, Isanda (2022)
The purpose of the study was to establish the challenges deaf trainees face in their social interactions. The study focused on St. Angela Mu mias Vocational School for the Deaf, Kakamega County. The study was an chored on the Theory of Mind by David Premack (1978). A case study des ign was adopted. The study target was 103, including 95 deaf trainees, one principal, and 7 trainers. Purposive sampling technique was emplo yed to select 3 trainers and the principal, while simple random sampli ng was used to select 39 deaf trainees. This study adopted a mixed-met hods data collection approach. Questionnaires comprising both open-end ed and close-ended questions were used to collect data from the princi pal and deaf trainees. In contrast, semi-structured interview schedule s were used to collect primary data from trainers. Quantitative data w as coded and analyzed using Statistical Package for Social Sciences (S PSS version 21). Descriptive data was represented in the form of mean, median, mode, correlation, frequency distribution tables, graphs, pie charts, and percentages. Qualitative data were coded systematically b y hand, analyzed thematically and presented in narrative form. The fin dings revealed that only 27.8 % of deaf trainees interacted with the h earing trainees and they also do not share their problems and secrets. Based on the results, the study recommends that the government, throu gh the Ministry of Education, decentralize sign language training to t he villages and community settings to assist in enhancing communicatio n between the Deaf and the hearing.